Characterization of radionuclide activity concentrations and lifetime cancer risk due to particulate matter in the Singrauli Coalfield, India - Yadav, A.K.; Hopke, P.K. (Springer Science and Business Media Deutschland GmbH, 2020)
In this study, the activities of 40K, 210Pb, 232Th, 234U, 235U, and 238U in size-segregated particulate matter (PM) were measured in the Singrauli Coalfield, India. Different isotopic compositions were found relative to natural uranium ratios. The radioactivity concentration ratios in different PM sizes [PM2.5, PM10, and suspended particulate matter (SPM)] suggested that anthropogenic sources affected the uranium isotopic compositions in the area. A different isotopic composition from the natural uranium composition was found. The correlation coefficients between the measured isotopes (40K, 210Pb, 232Th, 234U, 235U, and 238U) and meteorological factors were calculated. PM emissions were affected by the meteorological conditions, which in turn, influenced the U and Th concentrations in PM. The 232Th/238U activity ratio in particulate matter was between 0.20 and 1.54 with an average value of 0.9 ± 0.5, 0.2 to 1.1 (0.8 ± 0.7), and 0.2 to 1.2 with an average value of 0.8 ± 0.8 in PM2.5, PM10, and SPM, respectively. These range were quite different from the average crustal ratio of 3.5, indicating that the 238U concentrations were elevated in this region relative to Th. However, compared with Th, the dose contribution of U to the public was negligible. The average effective dose in public owing to inhalation of natural radioactive 40K, 210Pb, 232Th, and 234U, 235U, and 238U in the atmosphere was between 0.03 and 327 nSv year−1. These doses associated with the inhalation of particulate matter were lower than world airborne reference value as reported by UNSCEAR (2000a). [Figure not available: see fulltext.]. © 2020, Springer Nature Switzerland AG.
Keywords: Radioactivity concentrations; Particulate matter; Gamma radiation